The Toronto District Labour Council and Independent Political Action: Factionalism and Frustration, 1900-1921 - Piva, Michael J. (Labour / Le Travail, 1979)
This article examines the political debate within Toronto's District Labour Council (DLC) from 1900 to 1921. It argues that divisive factors within the Council hindered the emergence of an effective third party alternative in the city. The majority of the delegates to the DLC favoured the formation of a labour party controlled by trade unionists. The Council fostered the formation of such a party, but the combined opposition of left-wing delegates, who advocated affiliation with the Socialist and later the Social Democratic Parties, and right-wing delegates, who opposed third party electoral action of any kind, prevented the DLC from affiliating or working too closely with the various labour parties. During the war the socialist and labourite delegates within the Council joined forces to promote a reorganized and more broadly based Independent Labour Party, but, again, severe internal conflict prevented the ILP from winning significant electoral support in Toronto.